MHz-repetition-rate, sub-mW, multi-octave THz wave generation in HMQ-TMS - Buchmann, Tobias Olaf; Kelleher, Edmund J.R.; Kaltenecker, Korbinian J.; Zhou, Binbin; Lee, Seung Heon; Kwon, O. Pil; Jazbinsek, Mojca; Rotermund, Fabian; Jepsen, Peter Uhd (Optics Express, 2020)
We demonstrate the first megahertz (MHz) repetition-rate, broadband terahertz (THz) source based on optical rectification in the organic crystal HMQ-TMS driven by a femtosecond Yb:fibre laser. Pumping at 1035 nm with 30 fs pulses, we achieve few-cycle THz emission with a smooth multi-octave spectrum that extends up to 6 THz at -30 dB, with conversion efficiencies reaching 10-4 and an average output power of up to 0.38 mW.We assess the thermal damage limit of the crystal and conclude a maximum fluence of ∼1.8 mJ cm-2 at 10 MHz with a 1/e2 pump beam diameter of 0.10 mm. We compare the performance of HMQ-TMS with the prototypical inorganic crystal gallium phosphide (GaP), yielding a tenfold electric field increase with a peak on-axis field strength of 7 kV cm-1 and almost double the THz bandwidth. Our results further demonstrate the suitability of organic crystals in combination with fibre lasers for repetition-rate scaling of broadband, high-power THz sources for time-domain spectroscopic applications.
Keywords: Average output power; Broadband terahertz sources (THz); High-power THz sources; Inorganic crystals; Optical rectifications; Organic crystal; Repetition rate; Spectroscopic application